Percutaneous trigger finger release - Pandey, BK; Sharma, S; Manandhar, RR; Pradhan, RL; Lakhey, S; Rijal, KP (Nepal Orthopaedic Association Journal, 2013)
BACKGROUND: Trigger finger is caused by formation of nodule or thickening of A1 pulley by its fibrocartilage metaplasia resulting in entrapment of the flexor tendon. Conservative treatment of this condition consists of NSAIDs, splint immobilization and steroid injection into the tendon sheath. Failure of the conservative treatment is the indication of an open release. Percutaneous release of trigger finger is advised by several authors. The purpose of this prospective study is to evaluate the results of percutaneous release of trigger finger with 18 gauge needle. METHODS: Fifty one patients with 58 trigger digits were treated by percutaneous release using 18 gauge needle under local anaesthesia. Patients were followed up for an average of 12 months. RESULTS: Overall, 97% achieved an excellent or good result. Two digits experienced recurrent symptoms and required an open release. There was no clinical evidence of digital nerve injury or tendon bowstringing. CONCLUSIONS: We recommend this technique as a safe and effective outpatient procedure for releasing trigger finger. DOI: http://dx.doi.org/10.3126/noaj.v1i1.8126 Nepal Orthopaedic Association Journal Vol.1(1) 2010